2018
DOI: 10.3846/btp.2018.09
|View full text |Cite
|
Sign up to set email alerts
|

Monetary Policy and the Causality Between Inflation and Money Supply in Indonesia

Abstract: Conceptually and empirically, inflation volatility in Indonesia is a monetary and fiscal phenomenon. This study focuses on the macroeconomic policy and public policy especially causality between two variables namely inflation and money supply in Indonesia. This study uses Indonesian macroeconomic data of inflation and money supply from the Bank of Indonesia publication during 2007.1–2017.7. Inflation is measured by the consumer price index, reflects the annual percentage change in costs of acquiring a basket o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 12 publications
(21 reference statements)
1
11
0
Order By: Relevance
“…One of the likely factors of this condition is the government' various economic rescue programs such as the tight money or contractive policy that was effective in taming the inflation rate. Besides, the Inflation Targeting Framework that was implemented by Bank Indonesia (the Indonesian central bank) since July 2005 (Bank Indonesia 2017) and the empowerment of the Regional Inflation Monitoring Team in each local region facilitated further the inflation control (Sasongko and Huruta 2018).…”
Section: Introductionmentioning
confidence: 99%
“…One of the likely factors of this condition is the government' various economic rescue programs such as the tight money or contractive policy that was effective in taming the inflation rate. Besides, the Inflation Targeting Framework that was implemented by Bank Indonesia (the Indonesian central bank) since July 2005 (Bank Indonesia 2017) and the empowerment of the Regional Inflation Monitoring Team in each local region facilitated further the inflation control (Sasongko and Huruta 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, Indonesia's lack of participation in the GVC turned out to make Indonesia experienced no impact. In other words, the absence of causality between the BI Rate and the Federal Fund Rate might occur because the Indonesian currency (Rupiah) was very rarely used as a reference by other countries, so that all forms of economic policy in Indonesia (specifically interest rates) could only affect economic con- In addition to gross domestic product and lack of Indonesian participation in GVC, money supply, and inflation were also able to cause movement in domestic interest rates (Caporale & Pittis, 1997;Duburcq & Girardin, 2010;Sasongko & Huruta, 2018). This can be seen in Figure 3.…”
Section: The Causality Of Bi Rate and Federal Fund Ratementioning
confidence: 99%
“…Meanwhile, the existence of expansionary monetary policy through the addition of foreign exchange into the money market accelerated bank lending and an increase in net foreign assets increased the money supply (Sasongko & Huruta, 2018). Theoretically, an increase in the money supply causes a decrease in interest rates, then make the LM (Liquidity and Money) curve shift to the right.…”
Section: The Causality Of Bi Rate and Federal Fund Ratementioning
confidence: 99%
See 1 more Smart Citation
“…GDP behaved insignificantly against money supply and inflation rate whereas interest rate and exchange rate have a significant influence on GDP. Sasongko and Huruta (2018) showed that there is a one-way causality between money supply and inflation in Indonesia. Denbel et al (2016) disclosed that economic growth affected by the change of money supply and inflation based on the VECM approach.…”
Section: Introductionmentioning
confidence: 99%